(untitled) (Journal of Engineering, 2011)
This study focused on treating wastewater to remove phosphorus by adsorption onto natural and local materials. Burned kaolin, porcelinite, bauxite and limestone were selected to be tested as adsorption materials.The adsorption isotherms were evaluated by batch experiments, studying the effects of pH, temperature and initial phosphorus concentration. The results showed that at pH 6, temperature 20°C and 300 mg/l initial phosphorus concentration; the sorption capacity was 0.61, 9, 10 and 13 mg/g at 10 h contact time, for burned kaolin, porcelanite, limestone and bauxite respectively. As the pH increased from 2 to 10 the removal efficiency for the materials differs in behaviour. The removal efficiency increased from 40 to 90 % for limestone, and decreased from 60 to 30 % for porcelinite. As for bauxite it increased from 60 to 90 % reaching pH 6 then decreased to 30%. Burned kaolin showed the lowest adsorption capacities in these tests. The adsorption isotherms showed that the Langmuir–Freundlich model significantly correlated the experimental data for porcelinite and bauxite, whereby the Freundlich model was best for limestone. The Freundlich and Langmuir–Freundlich models both fit for Burned kaolin. The results show that it is possible to adsorb phosphate from wastewater onto natural Iraqi material and their ability could be ranged as limestone> bauxite> porcelanite> burned kaolin.